Fabrication of debranched starch nanoparticles via reverse emulsification for improvement of functional properties of corn starch films. (July 2020) - Lin, Qianzhu; Ji, Na; Li, Man; Dai, Lei; Xu, Xingfeng; Xiong, Liu; Sun, Qingjie
Abstract: In this study, we present a simple and novel method for preparing debranched starch nanoparticles (DSNPs) via reverse emulsification by using waxy corn starch (WCS) as the raw material. The morphology and physicochemical properties of DSNPs were systematically investigated by dynamic light scattering, atomic force microscopy, transmission electron microscopy, X-ray diffraction, and differential scanning calorimetry. In contrast to the microscale range of native WCS, the average particle sizes of DSNPs were mainly in the nanoscale range of 130 nm–280 nm, and showed good monodispersity. All DSNPs samples showed a B + V-type crystalline structure, which is quite different from the A-type of WCS. Furthermore, the relative crystallinity of DSNPs increased from 39.8% to 57.4%. Compared with pure corn starch films, the tensile strength of nanocomposite films increased by 85.9% when the additive amount of DSNPs varied from 0 to 5%. In addition, water vapor permeability and oxygen transmission rate decreased by 30.94% and 79.31%, respectively. The new approach of synthesis starch nanoparticles by reverse emulsification will advance the research of carbohydrate nanoparticles. Graphical abstract: Image 1 Highlights: Debranched starch was used to prepare nanoparticles by reverse emulsification. The obtained starch nanoparticles are spherical with the size of 130–280 nm. The nanoparticles showed a B + V type crystalline structure. The relative crystallinity of nanoparticles were in the range of 41.2–57.4%. The nanoparticles could improve the functional properties of corn starch films.